EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM POSING TERHADAP HASIL BELAJAR SISWA SMP NEGERI 3 PAGARALAM - Susanti, Novi; Erviana, Ria (Jurnal Math-UMB.EDU, 2019)
ABSTRAKThis research is an experimental research, while the problem formulation in this study is the Problem Posing learning model is effective against the results of learning straight line equation material in class VIII of SMP Negeri 3 Pagaralam. This study aims to determine the effectiveness of the Problem Posing model for student learning outcomes in the material of Straight Line Equations in Class VIII of SMP Negeri 3 agaralam, with a sample of students including 21 experimental class students and 21 control class students, to measure student mathematics learning outcomes in research This is a written test in the form of essays which amounts to 5 questions. The hypothesis of this research is that the Problem Posing learning model is effective on the learning outcomes of straight-line equations in class VIII of SMP Negeri 3 Pagaralam. The results of students' mathematical test data with the Problem Posing learning model obtained an average of 70.5 and the average mathematics learning outcomes of students not with the Problem posing model of 65.08. By using the t-test statistical formula, we obtained a tcount of 3.50 and a table price of 1.725 with a significance level of 5%. So it can be concluded that the hypothesis formulated by researchers proved to be accepted, namely the Effective Problem Posing learning model for solving straight line equation problems in class VIII of SMP Negeri 3 Pagaralam.Â Keywords: Problem Posing learning model, Student Learning